Two cases of paradoxical hypothermia in a Sahara desert multi-stage ultramarathon - Elizabeth A. Kaufman; Grant S. Lipman; Louis J. Sharp; Brian J. Krabak (Emergency Care Journal, 2014)
Exertional hypothermia in a hot environment, a seemingly contradictory state, is a clinical presentation that has not been previously described in the medical literature. We present two cases of symptomatic hypothermia of 34-35°C (95°F) which resolved with ingestion of calories in otherwise healthy men competing in a multi-stage ultramarathon in the Sahara desert, Egypt 2012 with ambient temperatures of approximately 38-39°C (100- 102°F). Hypothermia is well documented in the medical literature as a presenting sign of hypoglycemia in both conscious and comatose patients. The mechanism by which hypoglycemia contributes to hypothermia is poorly understood, but may represent a compensatory response that reflects a decrease in energy demand during glucose deprivation. Wilderness medicine practitioners at endurance events should be cognizant of hypothermia as a potential presenting sign of hypoglycemia, as it can be empirically treated and rapidly reversed.